Risk behavior analysis in Indonesian logistic train level crossing - Dian Palupi Restuputri; Achmad Mahardhika Febriansyah; Ilyas Masudin (Logistics, 2022)
Background: At Indonesian level crossings, traversed by logistics trains, there are still frequent cases of accidents. The overall mishaps in 2020 were 199 cases of accidents at level crossings involving road drivers. Mental load factors affect the behavior of drivers on the road; Methods: this study, field observations and surveys were carried out using the Driver Behavior Question-naire (DBQ) and NASA TLX to measure mental load; Results: The results showed that 62% of drivers had a very high mental load factor. The mental load factors are effort, frustration, and temporal demand. Meanwhile, based on the results of DBQ, the type of behavior that is often carried out is Violation; Conclusions: From the results of field observations, it is also known that there is a significant influence between time and type of vehicle on violations. Thus, it was necessary to improve facilities and systems at level crossings to provide convenience and reduce the volume of transportation going through level crossings to reduce the risk of accidents and violations at level crossings.
Keywords: 650; driver behavior questionnaire; level crossing; workload mental; logistic train